Formulation and Characterization of Inter-Penetrating Network of Isabgol Husk Mucilage for Modified Release of Diclofenac Sodium - Ale, Yogita; Nainwal, Nidhi; Butola, Mansi; Rana, Shilpa; Kala, Shivani; Rawal, Vinni; Jakhmola, Vikash (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Diclofenac Sodium (DS), a Non-Steroidal Anti-Inflammatory Drug (NSAID) is widely used in inflammation and pain management. However, the drug has a short half-life of 1.2-2 hr therefore, frequent administration of DS is required. In this research paper Inter-Penetrating Network (IPN) microspheres of Diclofenac sodium were made using Isabgol husk mucilage and Polyvinyl Alcohol (PVA) to prolong the release of diclofenac sodium. Isabgol husk is widely explored as a natural, economical, biocompatible, and biodegradable polymer for the development of a modified-release drug delivery system. Materials and Methods: IPN microspheres were prepared using Isabgol husk mucilage and Polyvinyl alcohol by emulsion cross-linking method in the presence of DL glyceraldehyde as a cross-linker. Evaluation: Fourier Transform Infrared (FTIR) spectroscopy was performed to confirm the formation of an interpenetrating network. The chemical stability of the drug and its molecular dispersion in the IPN was validated by X-ray Diffraction (XRD) analysis. The prepared microspheres were evaluated for % yield, drug loading, entrapment efficiency, surface morphology, swelling index and in vitro drug release. Results: The percentage yield and drug entrapment efficiency of the formulations were found in between 66.33 to 95.345%, and 40.24 to 68.12% respectively. The SEM and light microscopy studies confirmed the formation of spherical IPN microspheres. The model kinetics of in vitro release data found Korsmeyer-Peppas as the best-fit model for drug release from IPN microspheres.
Keywords: Inter-Penetrating Network; Isabgol husk mucilage; Diclofenac Sodium; DL-glyceraldehyde; Polyvinyl Alcohol